2017
DOI: 10.5007/2175-7925.2017v30n1p65
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia de diferentes formulações de acaricidas sobre larvas de Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) e Rhipicephalus (Boophilus) microplus (Canestrini, 1887) (Acari: Ixodidae)

Abstract: ResumoO parasitismo por ácaros sempre foi objeto de preocupações e perdas relacionadas à produção animal, assim como à transmissibilidade de agentes etiológicos de importantes doenças; e aproximadamente 95% das formas evolutivas dos carrapatos em fase não parasitária encontram-se no ambiente. Com base na importância de se controlar estágios larvares dos ixodídeos no ambiente, este estudo avaliou a eicácia de acaricidas in vitro sobre larvas de Rhipicephalus (Boophilus) microplus e Rhipicephalus sanguineus. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The most common method of R. microplus control is the use of commercial acaricides. Unfortunately, the excessive use of these agents has imposed the selection of resistant parasites, also resulting in high residue levels in milk and meat (Souza et al, 2017). Camillo et al (2008), showed a lack of efficacy in more than 90% of the farms in Rio Grande do Sul, and this was also observed by Mendes et al (2007), in São Paulo, Brazil.…”
Section: Introductionmentioning
confidence: 97%
“…The most common method of R. microplus control is the use of commercial acaricides. Unfortunately, the excessive use of these agents has imposed the selection of resistant parasites, also resulting in high residue levels in milk and meat (Souza et al, 2017). Camillo et al (2008), showed a lack of efficacy in more than 90% of the farms in Rio Grande do Sul, and this was also observed by Mendes et al (2007), in São Paulo, Brazil.…”
Section: Introductionmentioning
confidence: 97%